Long-Term Effectiveness of Parent Education Using the “Baby Oral Health” Model on the Improvement of Oral Health of Young Children - Gajanan V. Kulkarni (International Journal of Dentistry)
Purpose. To determine the long-term effectiveness of comprehensive education given to parents and caregivers with respect to the incidence of preventable oral diseases, utilization of dental services, and retention of knowledge related to oral health. Methods. Group presentations on oral health were conducted for caregivers of infants (n=161) using an interactive audio-visual aid. Followup occurred at 18 months. A comparison group (n=181) was enrolled from the same community groups. Chi-square and Fisher’s exact tests were used to analyze findings. Results. There was a difference in caries incidence, knowledge levels of caregivers, and utilization of dental services (P<0.05) when comparing the SGB to the SGFU. Conclusions. One-time exposure to parent education using a comprehensive interactive audio-visual aid has an effect on reducing caries incidence and increasing dental utilization. While most knowledge is retained by parents, there is some attrition in the information retained over an 18-month time period. This emphasizes the importance of repeated reinforcement of the same concepts over a shorter time span.